Barong ket Dance in Ubud Bali: The Enculturation Process for the Implicated Young Generation to the Existence of Traditional Dance - Arista Pratama, Pande Putu Yogi; Cahyono, Agus; Jazuli, Jazuli (Universitas Negeri Semarang, 2021)
Adat Ubud Village as one of the villages in Ubud District, Gianyar Regency, Bali Province, historically it has been known as the center of natural and cultural tourism in Bali. Particularly in the development of cultural tourism, it has become a source of the village income as well as between generations in community members. The cultural tourism in this matter is in the form of barong ket dance performances that are performed in various characters and staged at various stages spread across the area of Ubud. This study aims to examine the problem of how the process of cultivating the barong ket dance to the younger generation in preserving and developing traditional arts so that it becomes a source of income that has economic value. The strategy used in analyzing and examining this research problem uses an enculturation approach. The research results show that; 1) The enculturation of the Barong ket dance that has developed in Ubud was carried out by inheriting a dance style that has been created by its elders. 2) style that has been inherited then developed again through the process of enculturation to young generations. 3) the result of the consistent enculturation process could have implications for the existence of the art of barong ket dance as well as an attraction for tourists who were visiting to Ubud area.